PENGARUH PENERIMAAN PAJAK REKLAME DAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BANYUMAS - setiatri, Regita tias; Lestari, hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Tax is one of the public role in regional autonomy and revenue in an effort to regional development. Tax is one of the biggest sources of income for the regions. The existence of tax also contribute to the economic growth and national development. Nation. Taxes provide a great role so that the Indonesian government continue to improve and optimize nilai-nilai as sources of income tax and revenue for the country. An advertisement tax and hotel tax is two out of eleven local taxes in the district of Banyumas included into the genuine revenue (PAD). Both the tax is a tax where the number of potential investors, a vendor, the tourism and hotels that are increasingly multiply in the Banyumas regency. Total revenues up and down and the realization that does not meet the target is a problem of the two tax. Revenue in the Banyumas regency 2017 hit a slump in years a keen. On the basis of a decrease in the amount of revenue Banyumas regency absorbing not maximal. Research aims to understand how big the influence of advertisement tax and the hotel on local revenue ( PAD ) Banyumas regency. This study using quantitative methods involving 56 respondents that is the employee badan banyumas financial districts. Based on the research, advertisement tax and tax hotel has an effect on local revenue of 17 %. While advertisement tax and the hotel simultaneously influence on local revenue. Recommendations or suggestions of the research that the agency should improve the supervision to the financial taxpayers advertisement the tax payers from hotel